The reproductive pattern of the white barrel jellyfish Rhizostoma pulmo (Cnidaria, Scyphozoa) in the gulf of Taranto (Ionian Sea) - MAMMONE, MARTA; BASSO, LORENA; RIZZO, LUCIA; ARAVIND, AMRUTHA; PAGLIARA, PATRIZIA; PIRAINO, STEFANO (Mediterranean Marine Science, 2024)
Understanding the mechanisms that lead to the proliferation of large jellyfish populations over time is crucial to prevent andmitigate any possible negative impacts on human activities and ecosystem functioning. Rhizostoma pulmo (Macri, 1778) is an outbreak forming species of the Mediterranean Sea that has been observed in anthropized areas including the Gulf of Taranto. To describe seasonal changes in the reproductive patterns of R. pulmo from May to December 2016, we measured jellyfish diameter, the number and diameter of oocytes using histological and biochemical analyses (lipids, carbohydrates, proteins, and organic matter), as well as the gonadal somatic index (GSI). Jellyfish size did not fluctuate considerably during the collection period, with specimens measuring between 19.5 and 38.2 cm in diameter. Our findings revealed a strong gonadal activity over the summer and a spawning event between September and October. Male and female gonad morphology was similar to other previously reported Rhizostomeae. Oocytes were categorized into three developmental classes, recognizable by their diameter and shape: <15 μm for pre-vitellogenesis, 15-30 μm for vitellogenesis, and >30 μm mature oocytes. The number of mature oocytes peaked in August, with smaller eggs recorded in May and October and larger eggs recorded near the end of the summer. The GSI fluctuated greatly between sampling dates, peaking in August. Lipid levels varied significantly throughout the sampling period, with the greatest value in May (277.26±98 μg lipid mg AFDW-1) and the lowest in September (70.36±41.5 μg lipid mg AFDW-1). Carbohydrates, proteins, and organic matter (62 ± 6 %) remained stable during the sampling period. The biochemical analyses of jellyfish sexual reproduction we report on here can be used as a tool for identifying jellyfish spawning periods and better understanding the reproductive process that control jellyfish population dynamics.